2014
DOI: 10.4049/jimmunol.1303164
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Scavenger Receptor Class B Type I Deficiency Exacerbates Endotoxic Shock and Precipitates Sepsis-Induced Mortality in Mice

Abstract: Scavenger receptor class B type I (SR-BI)–deficient mice display reduced survival to endotoxic shock and sepsis. The understanding of the mechanisms underlying SR-BI protection has been hampered by the large spectrum of SR-BI functions and ligands. It notably plays an important role in the liver in high-density lipoprotein metabolism, but it is also thought to participate in innate immunity as a pattern recognition receptor for bacterial endotoxins, such as LPS. In this study, we sought to determine the tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
(43 reference statements)
1
26
0
4
Order By: Relevance
“…It is worth noting that the SR-BI fl/fl mice display hypomorphism with a 90% decrease in SR-BI expression globally (48), which may contribute to the differential inflammatory response between the hypomSR-BI ∆AC mice and our adrenal-specific SR-BI -/-mice. For example, a decrease in SR-BI expression in the liver impaired LPS clearance, which promotes inflammatory response (29,31). In support of this speculation, an earlier study showed that mice with a dimerization-deficient glucocorticoid receptor (GR dim ) display uncontrolled IL-6 production but has minor effects on TNF-α production in response to LPS (49).…”
Section: Pathogenesis Caused By Relative Adrenal Insufficiencymentioning
confidence: 90%
See 2 more Smart Citations
“…It is worth noting that the SR-BI fl/fl mice display hypomorphism with a 90% decrease in SR-BI expression globally (48), which may contribute to the differential inflammatory response between the hypomSR-BI ∆AC mice and our adrenal-specific SR-BI -/-mice. For example, a decrease in SR-BI expression in the liver impaired LPS clearance, which promotes inflammatory response (29,31). In support of this speculation, an earlier study showed that mice with a dimerization-deficient glucocorticoid receptor (GR dim ) display uncontrolled IL-6 production but has minor effects on TNF-α production in response to LPS (49).…”
Section: Pathogenesis Caused By Relative Adrenal Insufficiencymentioning
confidence: 90%
“…Thus, the less SR-BI -/-mice death was likely caused by the difference in strain background between the SR-BI -/-(129/B6 mixed background) and wild-type control mice (B6 background) (27). Gilbert et al (31) recently assessed the protective function of adrenal SR-BI using Sf1CreSR-BI fl/fl conditional knockout mice (hypomSR-BI ∆AC ) in B6 background and showed that the hypomSR-BI ∆AC mice lack inducible corticosterone production upon CLP challenge, and the mice are susceptible to CLP-induced animal death. These findings are consistent with our observations.…”
Section: Pathogenesis Caused By Relative Adrenal Insufficiencymentioning
confidence: 96%
See 1 more Smart Citation
“…Los niveles plasmáticos de LPS son particularmente importantes en algunas enfermedades como la sepsis, en las cuales se ha observado que el receptor para las HDL, SR-B1, controla la respuesta frente a la endotoxemia, reduciendo la activación de NF-κB (44). De hecho, en ratones con deficiencia en el receptor SR-B1, hay una menor sobrevida cuando se retan con LPS, sugiriendo un papel protector frente a la sepsis (45). Por otra parte, la expresión del TLR4 se ve disminuida en monocitos activados por LPS y tratados con ApoA-I, en los cuales la integridad de las balsas lipídicas se ve afectada por la inducción de flujo de colesterol (46), lo que sugiere que las HDL pueden estar induciendo un cambio funcional en estas células, disminuyendo la respuesta inflamatoria frente al LPS.…”
Section: Capacidad De Unión Y Neutralización Del Lpsunclassified
“…SR-BI knockout mice displayed extreme phenotypes of endotoxic shock and sepsis. Gilibert et al [16] demonstrated that the main role of SR-BI in host defense against endotoxic shock is related to its expression in the adrenal cortex. After endotoxic shock or bacterial infection, adrenal SR-BI, a key component of the hypothalamicpituitary-adrenal axis, effectively provides glucocorticoid-dependent host defense.…”
Section: Sr-bi and Infectious Diseasesmentioning
confidence: 99%